Boko Haram insurgency and livelihood vulnerability of rural households in Northern Adamawa State, Nigeria - Ahmadu Abubakar Tafida; Abdullahi Liman Tukur; E. F. Adebayo; A. A. Ndaghu; J. I. Onu; J. A. Momodu (Research in Globalization, 2023)
This study examines the vulnerability of rural households in eight selected insurgency-affected communities using the household vulnerability index with particular consideration to six main components of socio-demographics, healthcare, food security, water resources, conflicts and marketing, and access to finance as effect factors caused by Boko Haram Insurgency. Primary data used for the analysis were generated using an interview schedule among 280 household respondents in eight communities, selected using a purposive random sampling technique in July-September 2019. Livelihood Vulnerability Index (LVI) was used to analyse the data. The result showed that Gulak, Shuwa, Vih, and Lughu were the most vulnerable communities. The major components that contributed substantially to the overall LVIs were the conflict index, market, and financial index. The results have implications for adaptive and household resilient projects by the government and other humanitarian organizations for specific target interventions in the area. The insurgency has adversely affected rural households in Adamawa State, North East Nigeria. Therefore, enhancing infrastructure facilities, provision of basic amenities, access to market and finance, and improving the security architecture of the region will go a long way in addressing the plight and vulnerability of the people.
Keywords: 330; Community; Farming households; Insurgency; Rural areas; Vulnerability